Antiobesity Effect of Lacticaseibacillus paracasei LM-141 on High-Fat Diet-Induced Rats through Alleviation of Inflammation and Insulin Resistance. (18th April 2023) - Wu, Ching-Shuang; Lin, Chih-Chieh; Hsieh, Feng-Ching; Wu, Tai-Yun; Fang, Ai-Hui
Abstract : In this study, we set out to evaluate the antiobesity activities of our newly isolated Lacticaseibacillus paracasei LM-141 (LPLM141) using a high-fat diet (HFD)-fed rat model. Male Sprague–Dawley rats were fed with a HFD with or without low-dosage (2 × 10 7  CFU/day per rat) or high-dosage (2 × 10 9  CFU/day per rat) LPLM141 for 14 weeks. The results showed that administration of LPLM141 significantly decreased body weight gain, liver weight, adipose tissue weight, and epididymal white adipocyte size increased by HFD feeding. The abnormal serum lipid profile induced by HFD feeding was normalized by administration of LPLM141. The enhanced chronic low-grade inflammation in HFD-fed rats was reduced by LPLM141 supplementation, as reflected by decreased serum lipopolysaccharide (LPS) and monocyte chemoattractant protein-1 (MCP-1) levels, reduced macrophage infiltration in adipose tissue, and increased serum adiponectin concentration. In addition, the elevations of proinflammatory cytokine genes and suppression of PPAR- γ mRNA in adipose tissues of rats fed with a HFD were markedly reversed by LPLM141 administration. Oral administration of LPLM141 induced browning of epididymal white adipose tissue (eWAT) and activation of interscapular brown adipose tissue (iBAT) in rats fed with HFD. Consumption of LPLM141 exhibited a significant amelioration in insulin resistance, which were mechanistically caused by downregulation of the serum leptin level and upregulation of hepatic IRS-1 and p-Akt protein expressions, in HFD treated rats. LPLM141 consumption significantly decreased hepatic lipogenic gene expressions and preserved liver function stimulated by HFD treatment. Administration of LPLM141 obviously mitigated hepatic steatosis observed in HFD feeding rats. Our current findings shed light on LPLM141 supplementation that exhibited an antiobesity effect in HFD-fed rats by alleviating inflammation and insulin resistance, which further highlighted the potential of utilizing LPLM141 as a preventive/therapeutic probiotic agent for obesity.